DEVELOPING INFOGRAPHICS FOR TEACHING SPEAKING IDEAS BY USING CAKEAPP FOR TOURISM STUDENT IN THE FIRST SEMESTER OF GRADE 12 - Sasmitha, Ketut Aya; Utami, IGA Lokita Purnamika; Agustini, Dewa Ayu Eka (Yavana Bhasha : Journal of English Language Education, 2025)
Nowadays, incorporating technology into language instruction is crucial for enhancing students' speaking abilities, particularly in a professional setting. One of the fundamental skills in learning English is speaking, which is crucial for students in the tourism industry attending vocational high schools (SMK). This is due to the fact that the tourism industry needs employees who can interact with foreign visitors in a variety of service contexts. This study employs the ADDE (Analysis, Design, Development, and Evaluation) learning approach in conjunction with the design and development (DnD) model put forth by Richey & Klein, (2005). The goal of the design and development strategy is to produce an attractive infographic that will aid English teachers at Buleleng's vocational high schools in better understanding how to teach speaking with CakeApp. The goal of this project is to create infographics that teach speaking skills to SMK Pariwisata class XII students using the Cakeapp application. In addition, the results of expert validation show that the resulting infographics are of very high quality, with an average validation value of 91.5% given by experts. Based on these findings, it shows that the use of CakeApp-based infographics helps tourism students practice speaking skills effectively. The practical implication of this study is that teachers at tourism vocational schools can use this CakeApp-based infographic to support students' speaking learning process in class.